Potensi Getah Perca Indonesia Sebagai Bahan Baku Getah Perca Kedokteran Gigi - Kosterman Usri; Nina Djustiana; Elin Karlina (Jurnal Material Kedokteran Gigi, 2018)
Gutta percha is used for many functions in dentistry but the most popular is the root canal filler. This root canal filler is not a pure gutta percha but mixed with other materials, such as zinc oxide, wax, resi, and metal salts. The raw material of gutta percha dentistry is obtained from gutta percha tree (Palaquium gutta Baill) which in Indonesia has been cultivated in commercial scale since 1901 in Cipetir Sukabumi, in this location since 1921 is also equipped with its processing plant. This condition is very supportive if that gutta percha will be used as raw material of gutta percha dentistry. However, this material is a raw material that needs to be mixed with other materials in order to conform the standardization in dentistry, for that needed a series of research to be able to make gutta percha dentistry in Indonesia.